2006
DOI: 10.1096/fj.05-5058fje
|View full text |Cite
|
Sign up to set email alerts
|

A transport mechanism for NAADP in a rat basophilic cell line

Abstract: NAADP is a second messenger that releases Ca2+ from intracellular stores. Surprisingly, it has been recently shown that extracellular application of NAADP is capable of inducing intracellular Ca2+ release. This is particularly important since the only mammalian enzymes known to catalyze the synthesis of this second messenger are located extracellularly. In the present manuscript, we have investigated whether mammalian cells possess a transport system capable of transporting this highly charged molecule into ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 38 publications
7
31
0
2
Order By: Relevance
“…That NAADP can be efficiently transported into cells has been shown in a rat basophilic cell line and a neuroblastoma cell line, resulting in elevation of intracellular Ca 2ϩ (24). We have also observed that ␤-cells are permeable to exogenous NAADP, such that external application can induce a pattern of Ca 2ϩ signals similar to that stimulated by GLP-1 (3).…”
Section: Nicotinic Acid Adenine Dinucleotide Phosphate (Naadp)supporting
confidence: 68%
“…That NAADP can be efficiently transported into cells has been shown in a rat basophilic cell line and a neuroblastoma cell line, resulting in elevation of intracellular Ca 2ϩ (24). We have also observed that ␤-cells are permeable to exogenous NAADP, such that external application can induce a pattern of Ca 2ϩ signals similar to that stimulated by GLP-1 (3).…”
Section: Nicotinic Acid Adenine Dinucleotide Phosphate (Naadp)supporting
confidence: 68%
“…To investigate this possibility, we examined whether there is any interdependence between cADPR and NAADP production by taking advantage of transporting cADPR and NAADP to LAK cells (supplemental Fig. S1) like other cells known to be transported (35)(36)(37). The addition of exogenous cADPR to LAK cells enhanced intracellular NAADP levels, whereas the addition of NAADP failed to increase intracellular cADPR levels (Fig.…”
Section: Treatment Of Lak Cells With Il-8mentioning
confidence: 99%
“…It is difficult to envision how cADPR and NAADP can function inside the cell if they are generated by ectoenzymes. Several studies suggest that cADPR and NAADP are directly transported by CD38 or more likely by nucleotide transporters into the cytosol [10][11][12][13][14]. So far, in many cell types, responding to extracellular NAD + with an increase in [Ca 2+ ] i , conversion of NAD + to the Ca 2+ mobilizer cADPR [14][15][16][17][18] has been implicated as the principal mechanism leading to the rise in [Ca 2+ ] i .…”
Section: Introductionmentioning
confidence: 99%